2013
DOI: 10.1021/nn4014005
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Etching of Gold within Nanoshaved Self-Assembled Monolayers

Abstract: Wet etching of metal substrates with patterned self-assembled monolayers (SAMs) is an inexpensive and convenient method to produce metal nanostructures. For this method to be relevant to the fabrication of high precision plasmonic structures, the kinetics of nanoscale etching process, particularly in the lateral direction, must be elucidated and controlled. We herein describe an in situ atomic force microscopy (AFM) study to characterize the etching process within patterned SAMs with nanometer resolution and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…In particular, ferrocene-terminated alkanethiol (FcCnSH) molecules on gold substrates has provided with a simple and stable way to prepare tuneable films [4][5][6]. Furthermore, the presence of this electroactive moiety on the substrate has put forward significant advances to improve the protection against corrosion [7,8], to understand the electron transfer mechanisms [9][10][11], to enhance the performance of bioelectrochemical devices [12][13][14][15][16], and to exploit molecular electronics [17][18][19][20][21][22]. The stability of this surface modification relies on the strong interaction between the thiolated adsorbate and the gold substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, ferrocene-terminated alkanethiol (FcCnSH) molecules on gold substrates has provided with a simple and stable way to prepare tuneable films [4][5][6]. Furthermore, the presence of this electroactive moiety on the substrate has put forward significant advances to improve the protection against corrosion [7,8], to understand the electron transfer mechanisms [9][10][11], to enhance the performance of bioelectrochemical devices [12][13][14][15][16], and to exploit molecular electronics [17][18][19][20][21][22]. The stability of this surface modification relies on the strong interaction between the thiolated adsorbate and the gold substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Jana et al [18] have reported the anisotropic etching of Au spheroid to spherical nanoparticles using CN -. Electrochemical oxidation to Au crystals also has been reported [19,20]. Pradeep et al have used CuCl2 as an etchant for the anisotropic etching of Au nanorods, and selective etching of body and tip of the nanorods have been demonstrated [21].…”
Section: Introductionmentioning
confidence: 99%
“…Researches on the electrochemical behavior of redox active self‐assembled monolayers (SAMs) have been coming up since much time. The study of the interfacial electron transfer has derived in relevant advances concerning the protection against corrosion 1, electron transfer theory 2, bioelectrochemistry 3, and molecular electronics 4. Mixed SAMs, i.e.…”
Section: Introductionmentioning
confidence: 99%